Directed energy deposition of metals: processing, microstructures, and mechanical properties - Li, Shihao (2022)
Amongst the many additive manufacturing (AM) techniques, directed energy deposition (DED) is a prominent one, which can also be used for the repair of damaged components. In this paper, we provide an overview on it, with emphasis on the typical microstructures of DED alloys and discuss the processing-microstructure-mechanical property correlations. Comparison is made with those manufactured using the conventional techniques and those obtained with laser beam powder bed fusion (LB-PBF). The characteristic solidification rates and thermal histories in DED result in distinct micro- and meso-structural features and mechanical performance, which are succinctly summarized. The potential of DED for manufacturing graded materials and for component repair is elaborated while highlighting the key-associated challenges and possible solutions. Modelling and simulation studies that facilitate an in-depth understanding of the DED technique are summarized. Finally, some critical issues and research directions that would help develop DED further and extend its application potential are identified.